1964
DOI: 10.3181/00379727-115-28826
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Cardiac Sympathetics on Synchrony of Ventricular Contraction.

Abstract: I t is generally accepted that excitation of the sympathetic innervation of the heart significantly alters myocardial excitability, conductivity and contractility. Actual experimental demonstration of each of these properties has occurred only within relatively recent years although the influence of the catecholamines has been known. Marked alterations in the rate of rise of ventricular systolic pressure and the rate of fall of diastolic pressure have led to the deduction that sympathetic excitation exerts an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1964
1964
1989
1989

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Randall and Priola (17,18) reported that an important consequence of sympathetic stimulation is improved synchrony of cardiac contractility, while Wallace et al (19,20) point out that patterns and rate of conduction through the myocardium undergo only negligible changes during sympathetic excitation. In view of the present findings, synchrony may conceivably be improved with relatively little change in heart rate or myocardial conduction.…”
Section: Discussionmentioning
confidence: 99%
“…Randall and Priola (17,18) reported that an important consequence of sympathetic stimulation is improved synchrony of cardiac contractility, while Wallace et al (19,20) point out that patterns and rate of conduction through the myocardium undergo only negligible changes during sympathetic excitation. In view of the present findings, synchrony may conceivably be improved with relatively little change in heart rate or myocardial conduction.…”
Section: Discussionmentioning
confidence: 99%